Intra-articular platelet-rich plasma versus hyaluronic acid in the treatment of knee osteoarthritis: a meta-analysis - Zhang HF; Wang CG; Li H; Huang YT; Li ZJ (Dove Medical Press, 2018)
Hua-feng Zhang,1 Chen-guang Wang,1 Hui Li,1 Yu-ting Huang,2 Zhi-jun Li1 1Department of Orthopaedics, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 2Cancer & Immunology Research, Children’s Research Institute, Children’s National Medical Center, Washington DC, USA Purpose: Platelet-rich plasma (PRP) and hyaluronic acid (HA) have been increasingly used in recent years to treat knee osteoarthritis (OA). However, whether PRP is superior to HA is controversial.Methods: We conducted an electronic search of PubMed, Embase, ScienceDirect, and Cochrane library. The pooled data were analyzed using RevMan 5.1.Results: Three prospective and ten randomized trials were identified. PRP injections reduced pain more effectively than HA injections in OA of the knee at 6 months (mean difference [MD]=-14.18; 95% confidence interval [CI]: -26.12 to -2.23; P=0.02; I2=95%) and 12 months (MD=-15.25; 95% CI: -22.17 to -8.32; P<0.01; I2=81%) of follow-up evaluated by Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain score, while the VAS showed no significant difference at 3 months (MD=-0.98; 95% CI: -2.55 to 0.59; P=0.22; I2=90%) and 6 months (MD=-0.82; 95% CI: -1.80 to 0.16; P=0.1; I2=83%). Additionally, similar results were observed for the function recovery according to the WOMAC function score and EuroQol-visual analog scales.Conclusion: The intra-articular injection of PRP was not obviously superior to HA in knee OA. Due to the limited quality and data of the evidence currently available, more high-quality randomized controlled trials are required. Keywords: knee, osteoarthritis, hyaluronic acid, platelet-rich plasma